Answer:
The answer is 27
Step-by-step explanation:
The reason being, you can solve this 2 ways.
1) Combine like terms, 7a-4a = 3a.
Now just substitute (a=9) into 3a.
3 * (9) = 27.
2) Or just substitute a = 9 into the original expression.
7 * (9) - 4 * (9)
= 63 - 36 = 27
Step-by-step explanation:
By Law of Indices, a^m / a^n = a^(m-n).
Therefore a² / a⁸ = a^(-6).
x = -6.
The answer is 62^ it reflects angle IK
Answer:
7x³y² - 3x²y² + xy - 5
Step-by-step explanation:
Add like terms.
5x³y² + 2x³y² = 7x³y²
-3x²y² = -3x²y²
-3xy + 4xy = xy
2 - 7 = -5
Put them all together.
7x³y² - 3x²y² + xy - 5